Rural Consumers’ Factors of Influence, Place of Influence, and Decision Making Process : An Exclusive Model Based Study - Prakash, H. S.; Begum, Mustiary (Indian Journal of Marketing, 2016)
In the recent past, consumers in India have been at a point where there is a multiplicative effect in income growth, aspirations, and changed consumption patterns across income level segments. Therefore, understanding the rural consumer behavior and the process of decision-making has acquired significant attention and there has been a rise in the importance of private corporate big giants as the rural consumers started buying/consuming everything that was meant for the urban market. Keeping these changes in mind, the present paper tried to ascertain whether - there is any significant difference of opinion between the genders regarding the decision making process; the paper intended to find the different factors’ (primitive) influence on the rural consumers and the places where these primitive factors influence; and also attempted to gain knowledge regarding the exclusive consumer decision making process of the rural consumer. The study took into account the opinion of 125 respondents from two taluks of Shimoga district, Karnataka. The data were analyzed with the help of SPSS v 20 software. Mean, standard deviation, chi-square, and factor analysis techniques were used to test the hypotheses, and based on the test results, an exclusive model (HSP Model) of rural consumers’ factors of influence, place of influence, and decision-making process was developed.